PENGARUH TELECOMMUTING, BURNOUT, DAN QUALITY OF WORK LIFE TERHADAP EMPLOYEE ENGAGEMENT DI PT UNITED TRACTORS TBK. - Erita Shafira Maharani (2023)
The type of research used by researchers is quantitative which aims to determine the effect of telecommuting on employee engagement, the effect of burnout on employee engagement, the effect of quality of work life on employee engagement, and the effect of telecommuting, burnout, and quality of work life simultaneously on employee engagement. This study uses primary data sources. The population in this study are permanent employees of PT United Tractors Tbk. in the operational department. The sample used amounted to 96 respondents. The sampling technique in this study used simple random sampling. The data collection carried out in this study was an online questionnaire via Google Form. This study used the SEM method with the SmartPLS software test tool. The research obtained results, namely the telecommuting variable had a positive and significant effect on employee engagement with an original sample value of 0.304, the burnout variable had a negative and significant effect on employee engagement with an original sample value of 0.227, the quality of work life variable had a positive and significant effect on employee engagement with the original sample value is 0.427, and the telecommuting, burnout, and quality of work life variables have an effect and are significant simultaneously on employee engagement.